International passanger survey at the Airport Debrecen – Main characteristics of departure visitors from AD - Palatinus , Brigitta (Applied Studies in Agribusiness and Commerce, 2014)
The main reason of the research is to make a survey of the habits of foreign visitors arriving in Debrecen by air and their satisfaction. What was experienced in 2013 regarding low foreign proportion is also noticable in 2014. In the examined two months, of the whole passenger traffic between London and Debrecen only 10-15% is tourism by foreign visitors. There was not any information before about consumption of tourists arriving in Debrecen by air. In the course of my research I was examining the main elements of consumptions. From the gathered infromation from the questionaires it can be ascertained that on many occasions service providers failed to accomplish satisfying levels, quality. Underachievement occured and the experience of the visitors was worse than their expectations. This gives reasons for the indicators detailed analysis. The results of the satisfaction test might be an essential basis to further develop the city’s tourist products and services in the future. Personal experience of either visitors satisfaction or dissatisfaction, gets stored as a memory which influences future decisions on travelling. Because of this the city has to make an effort to provide higher standards of quality to people travelling into Debrecen by air from the first moment of arrival till the last moment of departure and leave satisffied.